تأثير إستراتيجيات التعامل مع الأزمات و التماثل التنظيمي في إرتباط الفرد بوظيفته دراسة استطلاعية لأ راء عينة من كوادر كليات التجارة والادارة والاقتصاد في الجامعات الحكومية والاهلية في محافظة السليمانية أثناء انتشار مرض كوفيد١٩ - صالح, صلاح حمه سعيد حمه (Sulaimani Journal for Humanities, 2021)
The current research aims to shed light on the impact of strategies for dealing with Crisis and organizational symmetry through their used dimensions on the individual’s relationship to his / her function with its dimensions during the spread of disease Covid-19. Accordingly, a hypothetical scheme has been prepared that includes the research variables and their dimensions, as well as formulating a number of main hypotheses for the purpose of analyzing, The correlation and impact between the independent variables and the dependent variable, and the researcher relies on distributing the Electronic Questionnaire as a main tool for data collection in the (Google forms) Program, And it was distributed to a sample of scientific cadres in a group of similar colleges in providing educational services in public and private universities such as the College of Commerce with Administration and economy in Sulaimani governorate, and (113) copies of which are valid for statistical analysis were filled out, and a number of statistical tools and methods were used to test the hypotheses of the research through (SPSS v.26). The research concluded a set of conclusions, the most important of which: the results of the study showed that there are Statistically significant moral effects of strategies to deal with Crisis and Organizational Symmetry on the association of the individual with his function during the spread of disease(Covid 19) and this indicates of high level in the perception of the sample research for their reputation, scientific status and social status. The researcher also recommends the importance of formulating strategies to deal with Crisis from period to period so that the cadres feel loyalty, belonging, job similarity and the integrity of their career in order to increase their degree of association.
Keywords: Strategies for Dealing with Crisis; Organizational Symmetry; The IndividualsAttachment to His Job; Disease Covid19